A Study of the Impact of Emerging Digital Marketing Technologies on Consumer Behaviour - Liu, Yijia (International Journal of Global Economics and Management, 2024)
With the advent of the digital era, emerging digital marketing technologies have had a profound impact on consumer behaviour. This thesis explores the definition and classification of digital marketing technologies, analyses their specific impact on consumer behaviour, and delves into the relationship between technological adaptation and changes in consumer behaviour. The thesis provides an overview of how emerging technologies such as personalised marketing, social media marketing, augmented reality (AR) and virtual reality (VR) technologies, as well as voice assistants and smart home devices, are changing the way consumers make shopping decisions and interact with brands. The paper explores how these technologies are influencing consumers’ purchasing decisions by improving perceived convenience, enhancing user engagement and providing personalised experiences. At the same time, the paper discusses the challenges of data privacy protection, legal and regulatory compliance, and ethics, and looks at the future direction of technology development, emphasising the importance of striking a balance between innovation and privacy protection. By systematically analysing these issues, the paper provides valuable insights and recommendations for companies when formulating their digital marketing strategies, in order to drive sustainable market development and consumer experience.